Peri- and intra-nodular radiomic features based on 18F-FDG PET/CT to distinguish lung adenocarcinomas from pulmonary granulomas - Tian, Congna; Hu, Yujing; Li, Shuheng; Zhang, Xinchao; Wei, Qiang; Li, Kang; Chen, Xiaolin; Zheng, Lu; Yang, Xin; Qin, Yanan; Bian, Yanzhu (Frontiers in Medicine, 2024)
Objective To compare the effectiveness of radiomic features based on 18 F-FDG PET/CT images within (intranodular) and around (perinodular) lung nodules/masses in distinguishing between lung adenocarcinoma and pulmonary granulomas.Methods For this retrospective study, 18 F-FDG PET/CT images were collected for 228 patients. Patients diagnosed with lung adenocarcinoma (n = 156) or granulomas (n = 72) were randomly assigned to a training (n = 159) and validation (n = 69) groups. The volume of interest (VOI) of intranodular, perinodular (1-5 voxels, termed Lesion_margin1 to Lesion_margin5Lesion_margin1-5) and total area (intra-plus perinodular region, termed Lesion_total1-to Lesion_total5) on PET/CT images were delineated using PETtumor and Marge tool of segmentation editor. A total of 1037 radiomic features were extracted separately from PET and CT images, and the optimal features were selected to develop radiomic models. Model performance was evaluated using the area under the receiver operating characteristic curve (AUC).Good and acceptable performance was respectively observed in both the training (AUC=0.868, p<0.001) and validation (AUC=0.715, p=0.004) sets for the intranodular radiomic model. Among the perinodular models, the Lesion_margin2 model demonstrated the highest AUC in both sets (0.883 and 0.616, p<0.001 and p=0.122). Similarly, in terms of total models, Lesion_total2 model was found to outperform others in the training (AUC=0.879, p<0.001) and validation (AUC=0.742, p=0.001) sets, slightly surpassing the intranodular model.When intra-and perinodular radiomic features extracted from the immediate vicinity of the nodule/mass up to 2 voxels distance on 18 F-FDG PET/CT imaging are combined, improved differential